2016
DOI: 10.1016/j.jab.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Development of biocompatible nanogel for sustained drug release by overcoming the blood brain barrier in zebrafish model

Abstract: A potential delivery system has to be fabricated for crossing the blood-brain barrier (BBB) to reach the brain fluid for effective delivery of drugs for any neurological disorders. The present study is aimed for the delivery of donepezil through functionalized PNIPAM nanogel by overcoming the BBB using zebrafish model. We had synthesized the poly N-isopropyl acrylamide nanogels with 20 nm size for sustained drug release. The entrapment of donepezil in the nanogel was quantified as 87.5% by HPLC and its sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The coating with PS80 permitted the crossing of NG through the BBB. The toxicity of PS80 was previously established in zebrafish and optimized in this study [ 18 ]. 5 nl of NG, NG + Rh–B, or NG + Rh–B + PS80 were injected with a Femtojet microinjector (Eppendorf).…”
Section: Methodsmentioning
confidence: 99%
“…The coating with PS80 permitted the crossing of NG through the BBB. The toxicity of PS80 was previously established in zebrafish and optimized in this study [ 18 ]. 5 nl of NG, NG + Rh–B, or NG + Rh–B + PS80 were injected with a Femtojet microinjector (Eppendorf).…”
Section: Methodsmentioning
confidence: 99%
“…They reported that the nanoparticle altered neurotransmission in the zebrafish brain as it had an effect on the acetylcholine esterase activity. In an interesting work Sivaji et al [ 198 ] aimed to deliver donepezil, a well-established drug for Alzheimer’s disease, through functionalized poly N -isopropyl acrylamide nanogels PNIPAM nanogel to the brain. They reported the gel could overcome the BBB and also showed sustained drug release using zebrafish model.…”
Section: Nanoparticles Focused For Delivering Drug To the Brainmentioning
confidence: 99%
“…Hydrogel formed with PNIAM has been studied successfully in Zebrafish model for sustained drug release and compatibility. PNIAM hydrogel is a functionalized nanogel loaded with donepezil with polysorbate-80 57 .…”
Section: Nanogelsmentioning
confidence: 99%